Neuropsychology of this Century: Prospects and Challenges - Vlasyuk, Dmitro (Psychological Prospects Journal, 2018)
The unprecedented development of neuroscience in the early 21st century raises the problem of rethinking the research paradigm of modern neuropsychology. Since the establishment of objective neuropsychology, its main achievements lay in the field of clinical neuropsychology – detection of behavioral consequences of organic and physical brain damage.Numerous neuroscience studies within a number of research programs give new results that improve understanding of the neural foundations of the psyche. In the middle of the second decade of the century, it was announced the beginning of large-scale projects of brain research in the European Union (Human Brain Project /HBP) and the United States (Brain Research Through Advancing Innovative Neurotechnologies). Financial support has also been expanded for previously initiated public and private research projects, such as the Canadian program (Brain Canada) and the Allen Institute for Brain Science program. In the process of their implementation there are new technologies of diagnosis of individual characteristics of the nervous system appear and significantly improved the existing ones. The most promising methods are non-invasive neuroimaging based on functional magnetic resonance tomography and computed tomography scanning. It is also noted that there is a need for a harmonious combination of new and traditional research methods.This gives large data sets for their correlation with the peculiarities of mental processes and social behavior of the individual. In such a situation, the focus of neuropsychological research is shifting from traditional methods of clinical psychology of diagnosis and correction of nervous system disorders, improvement of cognitive and social adaptation of a person. Among the researchers there are discussions about the optimal choice and priority of promising research strategies, as well as long-term social consequences of the development of neuroscience.The current state of research strategies, projects in which they are implemented, the development of technologies for the study of the nervous system and the impact of the results on the improvement of human existence are discussed in the article. The article analyzes the problems of development of neuropsychology in Ukraine and considers the ways of participation of Ukrainian neuropsychologists in international research programs.
Keywords: contemporary neuropsychology, brain research projects, methods of neuroscience.